Monitoring of Market Prices, Characterization of Value Chains, Cost and Benefit Analysis and Adoption Evaluation - International Crops Research Institute for the Semi-Arid Tropics; Association Malienne d'Eveil au Développement Durable; Institut d'Economie Rurale (International Food Policy Research Institute, 2017)
This research aims to (1) monitor the market prices on quarterly basis in Bougouni and Koutiala, (2) make a comparative analysis of on-farm trials conducted in intervention zones of the project, (3) value chain analysis of main crops, and (4) make an adoption evaluation of technologies promoted by the project in Bougouni and Koutiala districts.